2002
DOI: 10.1111/j.1749-6632.2002.tb04496.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biological Characterization of Chromofungin, the Antifungal Chromogranin A (47‐66)‐Derived Peptide

Abstract: The antifungal peptide named chromofungin is the most active vasostatin-I-derived peptide, corresponding to the sequence 47-66 of chromogranin A. (1)H-NMR analysis revealed that it adopts a helical structure. The mechanism implicated in the interaction of chromofungin with fungi and yeast cells was studied by penetration of monolayers and confocal laser microscopy. Chromofungin is able to interact with the cell wall, to cross the plasma membrane, to accumulate in the microorganism, and to inhibit calcineurin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 5 publications
1
57
0
Order By: Relevance
“…A fragment encompassing the region 39-63 (CgA 39-63 ) could bind avb6 with an affinity 14-fold higher than that of CgA, whereas, a shorter peptide (CgA 38-47 ) was considerably less active (Table 1). These results suggest that the region 48-63, which contains an amphipathic a-helix [33], is very critical for the binding affinity. Accordingly, progressive deletion of the C-terminal residues from CgA 39-63 caused progressive loss of affinity (Table 1).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…A fragment encompassing the region 39-63 (CgA 39-63 ) could bind avb6 with an affinity 14-fold higher than that of CgA, whereas, a shorter peptide (CgA 38-47 ) was considerably less active (Table 1). These results suggest that the region 48-63, which contains an amphipathic a-helix [33], is very critical for the binding affinity. Accordingly, progressive deletion of the C-terminal residues from CgA 39-63 caused progressive loss of affinity (Table 1).…”
Section: Resultsmentioning
confidence: 68%
“…Structure-activity studies performed with short fragments of CgA showed that the CgA 39-63 sequence is sufficient for high affinity binding to avb6 (K i = 7 nM). Deletion of residues 47-63, known to form an amphipathic a-helix adjacent to RGD [33], caused a marked loss of affinity for avb6 and gain of affinity for other integrins. For example, while the CgA 39-63 fragment could recognize avb6 with an affinity 250-1,000-fold higher than that for avb3, avb5, avb8 and a5b1, deletion of the entire a-helix decreased the affinity for avb6 and markedly increased that for avb3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that recombinant VS-1 and the synthetic CgA 47-66 peptide, at 5-10 nM concentrations, can penetrate into monolayers of phospholipids, inducing conspicuous increases in the surface area in phosphatidylcholine, phosphatidylethanolamine, and phosphatidylserine monolayers [34]. Of note, CgA 47-66 is a cationic peptide with an amphipathic a-helical structure [33] typical of antimicrobial peptides able to penetrate plasma membrane [41]. Based on these observations, we speculate that the 47-78 domain of VS-1 interacts with fibroblast membrane phospholipids through the hydrophobic-amphipathic 47-66 region.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the domain 47-78 of VS-1 can interact with proteinase K-resistant structures. Since we previously showed that the region 47-66 of VS-1 contains an amphipathic a-helix that can interact with artificial monolayers of phosphatidylserine, phosphatidylcholine, and phosphatidylethanolamine [33,34], it is likely that these structures correspond to membrane phospholipids. These results do not rule out the possibility that VS-1 can also interact with membraneassociated proteins or other components after interactions with lipids in untreated cells.…”
Section: The C-terminal Domain Of Vs-1 Contains a Cell-binding Sitementioning
confidence: 99%
See 1 more Smart Citation